1999
DOI: 10.1063/1.1149662
|View full text |Cite
|
Sign up to set email alerts
|

Picosecond time-resolved electronic spectroscopy in plate impact shock experiments: Experimental development

Abstract: An experimental method was developed to perform picosecond time-resolved electronic spectroscopy in single-event, plate impact, shock wave experiments. Several experimental difficulties had to be addressed due to the fast time resolution ͑100 ps͒ and short time duration ͑12.7 ns͒ of such experiments. Procedures are described to address the following experimental issues: ͑i͒ synchronization of the light source, detection equipment, and the shock event within the experimental duration, ͑ii͒ incorporation of a Nd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…[1][2][3] Luminescence spectroscopy, one of these techniques, has been used to study structural changes in materials under dynamic compression and release. 1,4 -6 Ruby luminescence has been extensively studied under both static 7,8 and dynamic compression, and results are used for pressure calibration.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Luminescence spectroscopy, one of these techniques, has been used to study structural changes in materials under dynamic compression and release. 1,4 -6 Ruby luminescence has been extensively studied under both static 7,8 and dynamic compression, and results are used for pressure calibration.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, experimental techniques have only recently been developed to perform in situ studies of chemical transformations in shocks. [6][7][8] Molecular and atomic scale information are difficult to experimentally obtain, and theoretical studies are necessary in order to develop simple chemical pictures for the high pressure-temperature behavior of the phase transformations of carbon.…”
Section: Introductionmentioning
confidence: 99%
“…18 The earlier work demonstrated that synchronizing the impact event to the laser firing is preferable to synchronizing the laser to the impact event. Because the excitation laser works in a repetitive mode, the key issue was to correlate a single event measurement with the repetitive firing of the laser.…”
Section: Synchronizationmentioning
confidence: 99%